Understanding health systems, health economies and globalization: the need for social science perspectives - Murray Susan F; Bisht Ramila; Baru Rama; Pitchforth Emma (BMC, 2012)
Abstract The complex relationship between globalization and health calls for research from many disciplinary and methodological perspectives. This editorial gives an overview of the content trajectory of the interdisciplinary journal 'Globalization and Health' over the first six years of production, 2005 to 2010. The findings show that bio-medical and population health perspectives have been dominant but that social science perspectives have become more evident in recent years. The types of paper published have also changed, with a growing proportion of empirical studies. A special issue on 'Health systems, health economies and globalization: social science perspectives' is introduced, a collection of contributions written from the vantage points of economics, political science, psychology, sociology, business studies, social policy and research policy. The papers concern a range of issues pertaining to the globalization of healthcare markets and governance and regulation issues. They highlight the important contribution that can be made by the social sciences to this field, and also the practical and methodological challenges implicit in the study of globalization and health.